Immune and oxidative stress trade-offs in four classes of Ruffs (Philomachus pugnax) with different reproductive strategies - GA Lozano; DB Lank; Brianne Addison (2013)
Immunity and resistance to oxidative stress are two mechanistically related aspects of self-maintenance that are usually not studied together in connection to ecological or evolutionary relevant variables. Whereas many studies compare two sexes, here we use Ruffs (Philomachus pugnax (L., 1758)), a species in which males have three alternative reproductive morphs: independents, satellites, and faeders. Previous work suggested that immune function in Ruffs depends on energetic constraints or potential of injuries. Based on their behaviour and life history, the three male morphs and females can be placed on an ordinal scale with independents at one end and females at the other, and these two explanations predict opposite patterns along this continuum. Innate and cell-mediated immunity decreased along this axis from independents to females, supporting a risk-of-injury explanation over the energetic constrains hypothesis. No such pattern was evident for oxidative stress or resistance, and no relationship was detected between immunity and oxidative resistance or stress. Hence, during the breeding season immunity reflected the risk of injury, with faeders located in the immunological continuum between females and other male morphs. Species with alternative reproductive strategies provide particularly useful systems in which to address the evolution and ecology behind physiological mechanisms.